Multifactor Balanced Asymmetrical Factorial Designs of Type II - N. J. Wanyoike; Guangzhou Chen (International Journal of Mathematics And its Applications, 2025)
This manuscript gives methods of constructing multifactor BAFDs of type II. Multi-factor BAFDS of type II are constructed from two factor BAFDs. Two methods of construction are given. The first method is the product of balanced arrays which is similar to the product of orthogonal arrays defined by [4]. The second methods was given by [28] which generates a BAFD from two given BAFD's. These methods can provide efficient BAFD's if efficient two factor BAFD's are used. The designs constructed are balanced with orthogonal factorial structure.